Monte carlo simulation by code of MCNP and experimental check for measuring thickness of materials for the spec raltzrng system of MYO-101 - Loat, Bui Van; Hung, Nguyen Van; Phuong, Hoang Sy Minh (VNU Journal of Science: Mathematics - Physics, 2010)
Abstract